Improving Pedagogical Competence of Hindu Religious Education Teachers in Formulating Themes Based on Hindu Teachings for Middle School Character Development - I Gede Dharman Gunawan; Krisma Natalia; Ni Putu Sri Pinatih; Putu Cory Candra Yhani; Ni Wayan Sukraini; Beny Saputra; I Nyoman Urip (International Journal of Community Service Learning, 2026)
The development of digital technology presents new challenges for character education at the secondary level, particularly in Hindu Religious Education learning in Kapuas Regency. Teachers still face limitations in formulating learning themes rooted in Hindu values that are relevant to students' digital context. This community service activity aims to analyze the pedagogical competence of Hindu Religious Education teachers in designing reflective learning themes grounded in Hindu values through continuous training and mentoring. This activity uses a descriptive qualitative approach with a participatory-educational and empowerment design. The subjects of the activity were determined through purposive sampling, involving 35 Hindu Religious Education teachers at the junior high and senior high/vocational high school levels. Data were collected through a teacher needs questionnaire (20 items), an evaluation questionnaire based on the Technology Acceptance Model (19 items), a student perception questionnaire (21 items), classroom observations, focus group discussions, and documentation. Data were analyzed using quantitative, descriptive, and qualitative reflection. The results of the community service showed an increase in teachers' ability to formulate learning themes based on the values of Dharma, Satya, Ahimsa, Daya, Ksama, and Arjawa, as well as an increase in students' positive responses to teachers' teaching style after the training. The implications of this activity highlight the role of MGMP as a strategic collaborative forum for developing teacher competencies grounded in Hindu values in the digital era.